Epidemiology, prognosis, and clinical manifestation of cardiovascular disease in COVID-19. (2nd August 2020) - Capone, Valentina; Cuomo, Vittoria; Esposito, Roberta; Canonico, Mario Enrico; Ilardi, Federica; Prastaro, Maria; Esposito, Giovanni; Santoro, Ciro
ABSTRACT: Introduction: At the end of 2019, a novel coronavirus was identified as the cause of a pneumonia cluster in Wuhan, China. Since then, the contagion has rapidly spread all over the world resulting in a global pandemic. Since frequent cardiovascular (CV) system involvement has soon been detected in patients occurring coronavirus disease 2019 (COVID-19), we would provide a simple review available to cardiologists who are going to be involved in the management of COVID-19 patients from several levels: from diagnosis to prevention and management of CV complications. Areas covered: We investigate the role of CV diseases in COVID-19: from the incidence of CV comorbidities to their negative impact on prognosis. We also search Literature in order to identify the main CV manifestations in patients occurring virus infection and their management by cardiologists. Expert opinion: Specific treatments for CV involvement associated with COVID-19 are still debated. Results from ongoing trials are needed to further clarify issues about the therapeutic approach, which is constantly changing according to the continuous flow of published evidence. Finally, it seems necessary to sensitize all population to raise awareness on CV diseases in the COVID era, to hinder the underestimation of both new-onset acute CV diseases and the consequences of chronic mistreated CV diseases.